PENGUATAN KARAKTER JUJUR MELALUI PEMBELAJARAN SIROH PADA SISWA KELAS 3 MADRASAH IBTIDAIYAH - Zahwa Rahmania Sabrina (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
ABSTRACT Strengthening honest character at the Islamic elementary school (madrasah ibtidaiyah) level requires learning experiences that not only introduce moral values but also encourage students to internalize and apply them in their daily lives. This study explored how siroh learning facilitates the internalization of honest character among third-grade students at MIT Al-Muhajirin. A qualitative approach with a case study design was employed, involving eight students and one siroh teacher selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis to identify patterns emerging from the participants’ experiences. The findings indicate that siroh learning strengthens honest character through the integration of the Prophet Muhammad SAW’s exemplary narratives, reflection on the meaning of honesty, and the habituation of honest behavior in students’ daily lives. This process enables students not only to understand honesty as a moral concept but also to develop the awareness to practice it in everyday interactions with the support of teachers as facilitators, role models, and reinforcers of positive habits. The study highlights that siroh learning has the potential to serve as a pedagogical approach to Islamic character education by integrating meaningful learning experiences, exemplary role models, and continuous habituation. These findings provide a foundation for developing a more systematic siroh-based learning approach to foster a culture of honesty in Islamic elementary schools. ABSTRAK Penguatan karakter jujur pada jenjang madrasah ibtidaiyah memerlukan pengalaman belajar yang tidak hanya memperkenalkan nilai moral, tetapi juga mendorong peserta didik menghayati dan menerapkannya dalam kehidupan sehari-hari. Penelitian ini mengeksplorasi bagaimana pembelajaran siroh membentuk proses internalisasi karakter jujur pada siswa kelas III MIT Al-Muhajirin. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus yang melibatkan delapan siswa dan satu guru mata pelajaran siroh yang dipilih secara purposive. Data diperoleh melalui wawancara semi-structured dan dianalisis menggunakan analisis tematik untuk mengidentifikasi pola-pola yang muncul dari pengalaman partisipan. Temuan menunjukkan bahwa pembelajaran siroh menguatkan karakter jujur melalui keterhubungan antara narasi keteladanan Nabi Muhammad SAW, refleksi terhadap makna kejujuran, dan pembiasaan perilaku dalam konteks kehidupan siswa. Proses tersebut memungkinkan peserta didik tidak hanya memahami kejujuran sebagai konsep moral, tetapi juga membangun kesadaran untuk menerapkannya dalam interaksi sehari-hari dengan dukungan guru sebagai fasilitator, teladan, dan penguat pembiasaan. Penelitian ini menegaskan bahwa pembelajaran siroh berpotensi menjadi pendekatan pedagogis dalam pendidikan karakter Islam karena mengintegrasikan pengalaman belajar, keteladanan, dan pembiasaan secara berkesinambungan. Temuan ini memberikan landasan bagi pengembangan pembelajaran siroh yang lebih sistematis dalam membangun budaya jujur di madrasah.